Gender and media : representing, producing, consuming - Krijnen, Tonny; Bauwel, Sofie van (London : Routledge, 2015)
'Why do some TV genres have the label feminine or masculine? Why do we worry about boys playing video games too much while girls play just as often? Is the TV show Sex and the City empowering or not? Why are recent television shows like Desperate Housewives post-feminist television? Gender and Media explores these and other complex questions by offering a critical overview of the contemporary debates and discussions surrounding gender and mediated communication, and by providing student's with an overview of the current academic research on these topics. The book is divided into three parts: representing, producing, and consuming with each section made up of three chapters. The first chapter of each section attempts to answer the most basic questions:'Who is represented?','Who produces what?' and'Who consumes what?'. The second chapter of each section draws attention to the complexity of the relationship between gender and media, concentrating on the'why.' The third and final chapter of each section addresses the latest debates in the fields of media and gender, adding a vital layer of understanding of the topic at hand. This process is aided by text boxes, which provide some additional information on the most important concepts and topics and exercises, which help bridge the gap between theory and everyday life media practices. This will be an ideal textbook for students studying gender and media, and for general courses on gender studies, sociology, cultural studies and women's studies'--
Includes bibliographical references (pages 184-204) and index.
Keywords: Sex role in mass media; Women in mass media; Men in mass media